Convergence-based Analysis of Robustness to Delay in Anti-windup Loop of Aircraft Autopilot∗. Issue 9 (2015) - Andrievsky, Boris; Kuznetsov, Nikolay; Leonov, Gennady
Abstract: The windup phenomenon is interpreted as a consequence of the convergent property absence for system with a saturation. This makes it possible to use the frequency-domain criterion for analysis of anti-windup augmentation in the case of stable and marginally stable plants. Based on this approach, robustness of the systems with respect to time delay in the anti-windup loop is examined and the approach for an optimal choice of the static anti-windup gain is proposed. An application of the convergence-based anti-windup control strategy to aircraft flight control for the case of time-delay in the anti-windup loop is described and studied by simulations.